A Study on the Design and Construction of a Stove Utilizing Waste Oil as Fuel - Urhamdi, Nila; Bahri Widodo, Syamsul; Cut, Banta (Fakultas Teknik Universitas Samudra, 2024)
The history of stoves reflects significant development, starting from the use of simple hearths to the emergence of kerosene stoves, electric stoves, and gas stoves. In Indonesia, the use of gas stoves continues to rise, especially with the ongoing energy conversion initiatives by the government. However, limited access to gas fuel in remote areas remains a challenge, necessitating efforts to explore alternative fuels. Used cooking oil is a waste product that has the potential to pollute the environment and adversely affect human health; however, it can be utilized as a stove fuel. This study aims to design and test a burner stove that utilizes used cooking oil as fuel. The research method involves quantitative data obtained from burner stove testing. The results indicate that the efficiency of the stove achieved is between 10,03% - 10,41%.